A kind of iron aluminum spinel nitrogen doped biochar catalyst for plastic pyrolysis hydrogen production and its preparation method and application

The iron-aluminum spinel nitrogen-doped biochar catalyst prepared by the hydrothermal method solves the problems of high cost of precious metal catalysts and low activity of iron oxide composite alumina catalysts in the existing technology, and achieves efficient and low-cost plastic pyrolysis. Hydrogen production effect.

CN118874521BActive Publication Date: 2025-01-17GUANGDONG TECHNION ISRAEL INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411364514.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-17
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

In the existing plastic pyrolysis technology, precious metal catalysts are expensive, and the intrinsic activity of iron oxide composite alumina catalysts and the selectivity of catalytic hydrogen production are low, resulting in low hydrogen production and high cost.

Method used

A hydrothermal method was used to prepare an iron-aluminum spinel nitrogen-doped biochar catalyst. The catalyst is biochar-supported cubic phase FeAl2O4 ortho-spinel type oxide. The oxide loading is 15~80 wt.%, and the structural specific surface area is greater than 300 m2/g, with microporous and mesoporous microstructure.

Benefits of technology

It significantly reduces the amount of catalyst, increases the yield of hydrogen production from plastic degradation, and reduces the cost, which is even lower than that of precious metal-based catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874521B_ABST
    Figure CN118874521B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of waste plastic treatment, and discloses an iron-aluminum spinel nitrogen-doped biochar catalyst for pyrolysis of plastics to produce hydrogen, and a preparation method and application thereof. The iron-aluminum spinel nitrogen-doped biochar catalyst is prepared by a hydrothermal method using biochar as a substrate. The catalyst is a biochar-loaded cubic phase FeAl 2 O 4 Spinel oxides, in which the oxide loading is 15-80 wt.%, the iron element is tetrahedral divalent iron, and the specific surface area of ​​the structure is greater than 300 m 2 / g, and has both microporous and mesoporous microstructures. The cost of the present invention is significantly lower than that of noble metal-based catalysts; and the catalyst having microporous and mesoporous microstructures is more conducive to the mass transfer process of the reaction, greatly reducing the amount of catalyst used, and significantly increasing the output of hydrogen produced by plastic degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste plastic treatment, and specifically relates to an ferroaluminum spinel nitrogen-doped biochar catalyst and a preparation method and application thereof. Background Art

[0002] Plastics have become an indispensable part of life around the world, but they have also brought serious environmental problems. In this context, it is particularly important to efficiently recycle and treat waste plastics, which not only helps reduce carbon emissions, but also significantly reduces environmental pollution. Catalytic pyrolysis technology can convert waste plastics into high-value-added products such as fuel oil and hydrogen, but traditionally, efficient catalytic pyrolysis requires the use of expensive precious metal catalysts such as ruthenium and platinum. The high cost of catalysts limits the widespread application of the technology. Compared with precious metal catalysts, iron oxide (Fe2O3) composite alumina (Al2O3) catalysts are relatively low in cost, greatly reducing the economic burden of waste plastic pyrolysis technology. However, the iron in the iron oxide structure is octahedral trivalent iron, which will be reduced during the catalytic pyrolysis of plastics to produce hydrogen, and its intrinsic activity / selectivity for catalytic hydrogen production is relatively low; in addition, the specific surface area of ​​the iron oxide (Fe2O3) composite alumina (Al2O3) catalyst is usually not very large, and under high-temperature catalytic reaction conditions, it will agglomerate due to the Ostwald ripening phenomenon, affecting the catalytic pyrolysis effect. Chinese patent CN 115869952A discloses a catalyst for hydrogen production from plastic degradation, and its preparation method and application. The catalyst is prepared by a solvent thermal method to obtain an aluminum and iron precursor, and then calcined and quenched to obtain an aluminum oxide / iron oxide composite material containing hydroxyl groups and oxygen defects and having a heterojunction structure. The composite material is used as a catalyst for hydrogen production from plastic degradation. When 500 μg of plastic is fed and 10 mg of catalyst is fed, the catalytic reaction is carried out, and the maximum hydrogen production is 390.2 μL. Although this method avoids the use of expensive precious metal catalysts, it still has the problems of low hydrogen production and high catalyst cost. Summary of the invention

[0003] Aiming at the high cost of precious metal catalysts and the relatively low intrinsic activity and selectivity of catalytic hydrogen production of iron oxide composite alumina catalysts in the existing plastic pyrolysis technology, the present invention uses biochar as a substrate and obtains iron aluminum spinel nitrogen-doped biochar catalyst by a hydrothermal method. The catalyst is biochar-loaded cubic FeAl2O4 positive spinel oxide, the oxide loading is 15-80 wt.%, the iron element is tetrahedral divalent iron, and the specific surface area of ​​the structure is greater than 300 m 2 / g, and possesses both microporous and mesoporous microstructures.

[0004] The technical solution of the present invention is as follows:

[0005] A method for preparing an iron-aluminum spinel nitrogen-doped biochar catalyst comprises the following steps:

[0006] (1) preparing an aqueous solution of a nitrogen-containing water-soluble polymer, a ferrous salt and an aluminum salt, adding biochar to perform ultrasonic dispersion, and then adding a nitrogen-containing alkaline solution, and maintaining ultrasonic dispersion to obtain a mixture;

[0007] (2) The mixture is subjected to a hydrothermal reaction, and after the reaction is completed, the mixture is cooled and dried to obtain an iron-aluminum spinel nitrogen-doped biochar catalyst.

[0008] Preferably, the mass ratio of the nitrogen-containing water-soluble polymer to the biochar is 1:(0.05-2); the molar ratio of the ferrous salt to the aluminum salt is 1:2; and the molar mass ratio of the ferrous salt to the biochar is 1-4 mmol / g.

[0009] Preferably, the nitrogen-containing water-soluble polymer is one or two of polyvinyl pyrrolidone, polyacrylamide, polyethyleneimine, and chitosan; and the nitrogen-containing alkaline solution includes one or more of an aqueous ammonia solution, an ammonium salt aqueous solution, and an organic amine aqueous solution.

[0010] Preferably, the mass ratio of the nitrogen-containing water-soluble polymer to the biochar is 1:1; and the molar mass ratio of the ferrous salt to the biochar is 3 mmol / g.

[0011] Preferably, the ammonium salt aqueous solution is one or both of an ammonium carbonate aqueous solution and an ammonium bicarbonate aqueous solution, and the organic amine aqueous solution is one or more of an aqueous solution of trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, n-butylamine and cyclohexylamine.

[0012] Preferably, the ferrous salt is one or more of nitrate, sulfate, acetate, chloride, thiocyanate of divalent iron or their hydrates.

[0013] Preferably, the aluminum salt is one or more of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum chloride, aluminum bromide or their hydrates.

[0014] Preferably, the mass volume ratio of the biochar to the nitrogen-containing alkaline solution is 0.01-0.1 g / mL, and the concentration of the nitrogen-containing alkaline solution is 15-35 wt. %.

[0015] Preferably, the hydrothermal reaction conditions are: reaction temperature is 140±20° C., and reaction time is 20±5 h.

[0016] Preferably, the biochar is prepared by subjecting biomass powder to a carbonization reaction in an inert gas atmosphere at a reaction temperature of 700-900° C. for a reaction time of 0.5-4 h to obtain the biochar.

[0017] Preferably, the particle size of the biomass powder is 24-35 meshes, and the carbonization reaction conditions are: heating to 800±50°C at a heating rate of 10±5°C / min and reacting for 2±0.5h; the biomass is one or a mixture of two or more of wood, bamboo, straw, bagasse, rice bran, sawdust, fruit shells, ramie, and corn cobs.

[0018] Preferably, the inert gas atmosphere is one or more of nitrogen, argon and helium.

[0019] Preferably, the oxide loading in the prepared catalyst is 30-60 wt.%, preferably 35-50 wt.%, more preferably 40-45%.

[0020] Another purpose of the present invention is to protect the use of the iron-aluminum spinel nitrogen-doped biochar catalyst prepared by the above method for plastic pyrolysis to produce hydrogen, comprising the following steps:

[0021] The plastic is placed in a pyrolysis reactor, and the iron aluminum spinel nitrogen-doped biochar catalyst is placed in a thermal catalytic reactor. The pyrolysis reaction temperature is 600°C and the catalytic temperature is 800°C.

[0022] The catalytic mechanism of the present invention involves the interaction of the active iron center with the CH bonds of the PP pyrolysis vapor, which requires a suitable d-band structure for efficient catalysis. In the cubic FeAl2O4 spinel oxide, the iron element is tetrahedral divalent iron ( Figure 2 ), iron bonds with four oxygen atoms to form FeO4 tetrahedrons, which share corners with AlO6 octahedrons. Iron has a d band structure that is favorable for CH bond activation. The tetrahedral coordination environment of iron causes the d orbital to split into e and t2 energy levels, and the energy of the t2 orbital is higher than that of the e orbital due to the geometry of the tetrahedral ligand field. The high-energy t2 orbitals are more easily available for bonding interactions, allowing them to stabilize the transition state of CH bond cleavage from lateral overlap of π bonds, which means that tetrahedral divalent iron is more likely to undergo bonding interactions, that is, tetrahedral iron is more conducive to the breaking of CH bonds and the formation of more stable intermediates, reducing the activation energy barrier of the reaction, and ultimately increasing the yield of hydrogen produced by catalytic plastic degradation. In addition, the Fe-O bond length in the tetrahedral coordination of FeAl2O4 is shorter than that in the octahedral position. The Fe-O bond in the tetrahedral position is stronger and has more significant covalent bond characteristics; the shorter Fe-O bond length also enhances covalency and stabilizes the intermediates formed during the CH bond breaking process, reducing the dehydrogenation activation energy, and ultimately increasing the catalytic plastic degradation hydrogen production yield. The iron in the iron oxide structure is trivalent iron in the octahedral position. The octahedral coordination environment of iron leads to a different d band structure, which is relatively unfavorable for CH bond breaking. 2gThe orbitals are located at lower energy levels, reducing the availability of electrons for catalytic interactions. The longer Fe-O bond length also reduces covalency, reducing catalytic efficiency compared to the tetrahedral configuration.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention uses biochar as a substrate and obtains iron-aluminum spinel nitrogen-doped biochar catalysts through a hydrothermal method. The catalyst is a biochar-loaded cubic FeAl2O4 spinel-type oxide with an oxide loading of 15-60 wt.%. Its cost is significantly lower than that of precious metal-based catalysts. Due to the addition of a large amount of biochar, it is also cheaper than existing iron-aluminum oxide catalysts.

[0025] (2) The specific surface area of ​​the catalyst structure of the present invention is greater than 300 m 2 / g, which is beneficial to the exposure of active sites on the catalyst surface during the catalytic degradation of plastics; and the catalyst has microporous and mesoporous microstructures, which is more conducive to the mass transfer process of the reaction, which not only greatly reduces the amount of catalyst used, but also significantly increases the output of hydrogen produced by plastic degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the X-ray diffraction pattern of Example 1.

[0027] Figure 2 This is the X-ray photoelectron spectrum of the iron element in Example 1.

[0028] Figure 3 The X-ray photoelectron spectra of nitrogen element in Example 1 and Comparative Example 4 are shown.

[0029] Figure 4 This is the transmission electron microscope image of Example 1.

[0030] Figure 5 This is the nitrogen isothermal adsorption-desorption curve of Example 1.

[0031] Figure 6 This is the pore size-specific surface area increment distribution diagram of Example 1.

[0032] Figure 7 The thermogravimetric curves of Examples 1 to 4 under an oxygen atmosphere. DETAILED DESCRIPTION

[0033] The present invention is described in more detail below by way of examples, but is not intended to be limiting of the present invention.

[0034] Example 1

[0035] (1) Preparation of biochar substrate:

[0036] Weigh 1 g of pine biomass powder with a particle size of 24-35 mesh, transfer it to a nitrogen inert gas atmosphere, heat it to 800 °C at a heating rate of 10 °C / min and react for 2 h to obtain the biochar substrate;

[0037] (2) Preparation of iron-aluminum spinel nitrogen-doped biochar catalyst:

[0038] Prepare 30 mL of aqueous solution containing 50 mg of polyvinyl pyrrolidone, 0.15 mmol of ferrous sulfate, and 0.30 mmol of aluminum chloride, add 50 mg of the biochar substrate described in step (1) and perform ultrasonic dispersion for 0.5 h, then add 0.8 mL of ammonia solution (25 wt.%) and maintain ultrasonic dispersion for 10 min to obtain a mixture, then transfer the mixture to a hydrothermal reactor and perform hydrothermal reaction at 140°C for 20 h. After the reaction is completed, cool to room temperature and filter, dry and filter the obtained solid to obtain an iron-aluminum spinel nitrogen-doped biochar catalyst. The molar ratio of its metal iron and aluminum precursors is 1:2.

[0039] Figure 1 The X-ray diffraction results show that Example 1 is biochar-loaded cubic phase FeAl2O4 spinel-type oxide, corresponding to standard card PDF#34-0192, and the diffraction peaks at 2θ angles of 31.0, 36.5, 44.4, 55.1, 58.8 and 64.6° correspond to the (220), (311), (400), (422), (511) and (440) crystal planes, respectively. Figure 2 The X-ray photoelectron spectrum of iron shows that the iron is tetrahedral divalent iron. Figure 3 The X-ray photoelectron energy spectrum of nitrogen element shows that, different from Comparative Example 4, Example 1 has a high nitrogen content, including nitrogen oxide, graphitic nitrogen, pyrrolic nitrogen and pyridinic nitrogen, which mainly comes from the coordination of nitrogen in ammonia water / nitrogen-containing functional groups of nitrogen-containing water-soluble polymers with hydroxide and metal ions during the preparation process, and nitrogen oxide is formed by the lattice oxygen in FeAl2O4 spinel oxide anchored on the nitrogen active sites on the nitrogen-doped biochar; graphitic nitrogen shows that the nitrogen in ammonia water / nitrogen-containing functional groups of water-soluble polymers are also doped in the biochar structure. Figure 4 Transmission electron microscopy results show that the particles of FeAl2O4 spinel oxide are approximately between 10 and 100 nm. Figure 5 The nitrogen isothermal adsorption-desorption curve test shows that the specific surface area of ​​Example 1 prepared is as high as 355m 2 / g. Figure 6 The results of the mesopore diameter-specific surface area increment distribution diagram show that Example 1 has both microporous and mesoporous microstructures.

[0040] Example 2

[0041] In step (2), 30 mL of an aqueous solution containing 50 mg of polyvinyl pyrrolidone, 0.05 mmol of ferrous sulfate, and 0.10 mmol of aluminum chloride is prepared. The rest of the preparation process is basically the same as that of the above-mentioned Example 1. After the reaction is completed, an iron-aluminum spinel nitrogen-doped biochar catalyst can be obtained.

[0042] Example 3

[0043] In step (2), 30 mL of an aqueous solution containing 50 mg of polyvinyl pyrrolidone, 0.10 mmol of ferrous sulfate, and 0.20 mmol of aluminum chloride is prepared. The rest of the preparation process is basically the same as that of the above-mentioned Example 1. After the reaction is completed, an iron-aluminum spinel nitrogen-doped biochar catalyst can be obtained.

[0044] Example 4

[0045] In step (2), 30 mL of an aqueous solution containing 50 mg of polyvinyl pyrrolidone, 0.20 mmol of ferrous sulfate, and 0.40 mmol of aluminum chloride is prepared. The rest of the preparation process is basically the same as that of the above-mentioned Example 1. After the reaction is completed, an iron-aluminum spinel nitrogen-doped biochar catalyst can be obtained.

[0046] Thermogravimetric analysis of Examples 1 to 4 was performed in an oxygen atmosphere. Figure 7 , wherein the oxide loadings in the catalysts of Examples 1 to 4 are 41.2 wt.%, 17.3 wt.%, 30.6 wt.%, and 58.8 wt.%, respectively.

[0047] Comparative Example 1 (no aluminum salt added)

[0048] In step (2), 30 mL of an aqueous solution containing 50 mg of polyvinyl pyrrolidone and 0.45 mmol of ferrous sulfate is prepared. The rest of the preparation process is basically the same as that of the above-mentioned Example 1. After the reaction is completed, a spinel catalyst containing ferrosoferric oxide can be obtained.

[0049] Comparative Example 2 (without adding ferrous salt)

[0050] In step (2), 30 mL of an aqueous solution containing 50 mg of polyvinyl pyrrolidone and 0.45 mmol of aluminum chloride is prepared. The rest of the preparation process is basically the same as that of the above-mentioned Example 1. After the reaction is completed, an aluminum oxide-containing catalyst can be obtained.

[0051] Comparative Example 3 (different molar ratios of ferrous salt and aluminum salt)

[0052] In step (2), 30 mL of aqueous solution containing 50 mg of polyvinyl pyrrolidone, 0.30 mmol of ferrous sulfate, and 0.15 mmol of aluminum chloride is prepared, and the rest of the preparation process is basically the same as that of the above-mentioned Example 1. After the reaction is completed, an iron-aluminum spinel catalyst can be obtained. The molar ratio of the metal iron to aluminum precursor is 2:1.

[0053] Comparative Example 4 (No Nitrogen Doping of Iron-Aluminum Spinel)

[0054] Without step (2), the rest of the preparation process is basically the same as that of the above-mentioned embodiment 1. After the reaction is completed, a biochar-based catalyst can be obtained.

[0055] Experimental example

[0056] The generation device and detection device of rapid pyrolysis degradation of plastics are respectively a vertical microreactor (Rx-3050 TR, Frontier Laboratory, Japan) and a gas chromatography separation and detection (8890, Agilent, USA) coupling system. The system uses helium as a carrier gas with a flow rate of 156 mL / min, the plastic is polypropylene powder, the feed is 500 μg, and the catalyst is Examples 1 to 4 or Comparative Examples 1 to 4, and the feed is 5 mg. During the reaction, the pyrolysis reaction temperature of the upper layer of the vertical microreactor is 600°C, and the catalytic temperature of the lower layer is 800°C. During the detection, the gas products of the reaction are first separated by a chromatographic column (113-4362, Agilent) and detected by a thermal conductivity detector, with a reference flow rate of 20 mL / min. The initial temperature of the gas chromatograph column box is 40°C and maintained for 4 min, and is increased to 280°C at a heating rate of 6°C / min and maintained for 6 min. The quantification of hydrogen produced by catalytic degradation of plastics was carried out using the external standard method, and the hydrogen production rate was calculated according to Formula 1.

[0057] Hydrogen production rate (%) = catalytic hydrogen production (μL) / theoretical hydrogen production (μL) * 100% (Formula 1).

[0058] Table 1 Hydrogen production and hydrogen production rate of different embodiments and comparative examples for catalytic degradation of high-density polyethylene powder

[0059]

[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing an iron-aluminum spinel nitrogen-doped biochar catalyst for producing hydrogen by pyrolysis of plastics, characterized in that: The catalyst is nitrogen-doped biochar-loaded cubic FeAl2O4 spinel oxide, the catalyst contains nitrogen oxide, graphite nitrogen, pyrrolic nitrogen and pyridinic nitrogen, wherein the loading amount of the oxide is 30-60wt.%, and the iron element is tetrahedral divalent iron; comprising the following steps: (1) preparing an aqueous solution of a nitrogen-containing water-soluble polymer, a ferrous salt and an aluminum salt, adding biochar to perform ultrasonic dispersion, and then adding a nitrogen-containing alkaline solution, and maintaining ultrasonic dispersion to obtain a mixture; the molar ratio of the ferrous salt to the aluminum salt is 1:2; (2) subjecting the above mixture to a hydrothermal reaction at a reaction temperature of 140±20°C and a reaction time of 20±5 h; after the reaction is completed, cooling and drying are performed to obtain an iron-aluminum spinel nitrogen-doped biochar catalyst; The nitrogen-containing water-soluble polymer is one or two of polyvinyl pyrrolidone, polyacrylamide, polyethyleneimine, and chitosan; the nitrogen-containing alkaline solution includes one or more of ammonia solution, ammonium salt solution, and organic amine solution.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nitrogen-containing water-soluble polymer to the biochar is 1:(0.05-2); the molar mass ratio of the ferrous salt to the biochar is 1-4 mmol / g.

3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the biochar to the nitrogen-containing alkaline solution is 0.01-0.1 g / mL, and the concentration of the nitrogen-containing alkaline solution is 15-35 wt.%.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the nitrogen-containing water-soluble polymer to the biochar is 1:1; the molar mass ratio of the ferrous salt to the biochar is 3 mmol / g.

5. The preparation method according to claim 4, characterized in that: The ammonium salt aqueous solution is one or both of an ammonium carbonate aqueous solution and an ammonium bicarbonate aqueous solution, and the organic amine aqueous solution is one or more of an aqueous solution of trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, n-butylamine and cyclohexylamine; The ferrous salt is one or more of nitrate, sulfate, acetate, chloride, thiocyanate or hydrates thereof of divalent iron; The aluminum salt is one or more of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum chloride, aluminum bromide or their hydrates.

6. The preparation method according to any one of claims 1 to 5, characterized in that The preparation of the biochar is as follows: biomass powder is subjected to a carbonization reaction in an inert gas atmosphere at a reaction temperature of 700-900° C. and a reaction time of 0.5-4 h to obtain the biochar.

7. The preparation method according to claim 6, characterized in that: The particle size of the biomass powder is 24-35 meshes, and the carbonization reaction conditions are: heating to 800±50°C at a heating rate of 10±5°C / min and reacting for 2±0.5h; the biomass is one or a mixture of two or more of wood, bamboo, straw, bagasse, rice bran, fruit shell, ramie, and corn cobs.

8. The preparation method according to claim 7, characterized in that: The wood is sawdust.

9. The iron aluminum spinel nitrogen-doped biochar catalyst prepared by the method of claim 3, 4 or 5, characterized in that: The catalyst is a nitrogen-doped biochar-loaded cubic FeAl2O4 spinel oxide, which contains nitrogen oxide, graphite nitrogen, pyrrolic nitrogen and pyridinic nitrogen, and has a specific surface area of ​​more than 300 m 2 / g, and possesses both microporous and mesoporous microstructures.

10. The iron-aluminum spinel nitrogen-doped biochar catalyst prepared by the method according to any one of claims 1 to 8 is used for hydrogen production by pyrolysis of plastics, characterized in that: The catalyst is a nitrogen-doped biochar-loaded cubic FeAl2O4 spinel oxide, which contains nitrogen oxide, graphite nitrogen, pyrrolic nitrogen and pyridinic nitrogen, and has a specific surface area of ​​more than 300 m 2 / g, and possesses both microporous and mesoporous microstructures.

Citation Information

Patent Citations

  • Catalyst for hydrogen production through plastic degradation and preparation method and application thereof

    CN115869952A

  • Catalyst for preparing carbon nano tube through microwave catalytic pyrolysis of waste plastics as well as preparation method and application of catalyst

    CN115414937A

  • Biochar composite material loaded with iron-aluminum oxide and application of biochar composite material in coastal salinized soil improvement

    CN118064155A